SIDUMO REVISITED – THE JUDGMENT OF THE CONSTITUTIONAL COURT - MJ Boyens; Adriaan van der Walt (Obiter, 2015)
The primary purpose of this article is to revisit and reconsider the development of the review test set out in the Constitutional Court judgment of Sidumo v Rustenburg Platinum Mines Ltd ((2007) 28 ILJ 2405 (CC)) and consequently ascertain the correct approach to be adopted by our Labour Courts in the application of such test. The secondary purpose, entails the determination of the extent to which Labour Court judges interfere with the merits of awards and the resulting impact on the distinction between appeal and review. In order to establish whether the test for review has been correctly developed and to determine whether our review proceedings deter recurrent interference by our judges, an edifying consideration of judicial review in South Africa, an extensive analysis of various judgments pertaining to such development, followed by a comprehensive comparison with the United Kingdom`s application of review proceedings and judicial composition are made. The research methodology is based on a contour of Sidumo, commencing with the Sidumo judgment, followed by three contentious Labour Appeal Court judgments and concluding with a Supreme Court of Appeal judgment, which clarify the operation of the review test. The contour is interlinked with the notion of reasonableness. In a follow-up article a trilogy of LAC judgments that place a gloss on Sidumo will be analysed.